Albinism in Artocarpus integrifolia Linn. F. - a Case Study - Rao, P. S.; Murti, S. S. N.; Venkaiah, K. (Indian Forester, 1999)
Albino seedlings to the extent of 0.0004% are noticed in Artocarpus integrifolia. None of the albino seedlings survive, mainly because of chlorophyll deficiency which is probably a resultant of natural selfing. Seeds collected from particular locality alone showed albinism.